A100 ORAL VANCOMYCIN THERAPY FOR CLOSTRIDIOIDES DIFFICILE INFECTION AND RISK OF INFECTION WITH GRAM-NEGATIVE ORGANISMS. (26th February 2020) - Someili, A; Alosail, A; Brooks, A; Irfan, N; Leto, D; Hadzic, A; Alajmi, A; Mertz, D; Bader, M
Abstract: Background: Vancomycin is the recommended first-line therapy for mild to severe Clostridioides difficile infection (CDI). However, oral vancomycin is associated with disruption of the indigenous microbiota, predisposing patients to overgrowth of endogenous pathogens such as vancomycin-resistant enterococci. Aims: The primary objective of the study is to examine the effect of the treatment regimens of CDI on the risk of infection with gram-negative organisms in adult patients treated for CDI. Methods: A retrospective cohort study of 319 adult patients treated for CDI at Hamilton Health Sciences in the year 2015. A multivariate logistic regression analysis was performed to determine if oral vancomycin-based therapy is associated with an increased risk of infection with gram-negative organisms after adjustment for other factors. Results: Eighty-one patients were excluded because of recurrent episodes of CDI within the same year or missing information. 238 patients were included in the final analysis. 48 (20.2%) patients had positive culture for gram-negative organisms after onset of CDI. Urine was the most common source for gram-negative organisms (39/48, 81.3%) followed by blood (8/48, 16.7%). The most common isolated gram-negative organisms were Escherichia coli (18/48, 37.5%) and Klebsiella pneumonia (9/48, 18.8%). The most common CDI treatment regimens were metronidazole monotherapy (137/238, 57.6%), vancomycin monotherapy (13/238, 5.5%), and combination therapy (88/238, 37.0%). Among patients who were treated with metronidazole monotherapy, vancomycin monotherapy, and combination therapy, 30(30/137, 21.9%), 3 (3/13, 23.1%), and 15 (15/88, 17.1%) had positive culture for gram-negative organisms, respectively ( P = 0.6). Ninety-seven (97/238, 40.8%) patients had severe CDI, 40 (40/97, 41.2%) were treated with metronidazole monotherapy, 5(5/97, 5.2%) with vancomycin monotherapy, and 52 (52/97, 53.6%) with combination therapy. 26 (26/141, 18.4%) and 22 (22/97, 22.7%) had positive culture for gram-negative organisms among patients with non-severe and severe CDI, receptively ( P = 0.7). In the multivariate analysis, neither type of CDI treatment regimen ( P =0.2, 95% CI 0.30–1.31) nor CDI severity ( P =0.4, 95% CI 0.67–2.69) was associated an increased risk of infection with gram-negative organisms after CDI onset. Conclusions: Contrary to the reported literature, we did not find that oral vancomycin-based CDI treatment was associated with increased risk of infection with gram-negative organisms. Funding Agencies: None